1. All I need to do is derive the 4th equation of motion being v2= v02+2aD from the second (t=(v-v0)/a) and third (D=1/2at2+v0t). 2. In this case D= (Ending-initial distance) V0= Initial Veolocity 3. By having the second equation solved for t I could substitute it in an completely eliminate time and I end up with D=1/2a((v-v0)/a))2+v0((v-v0)/a). Past this point I knwo to distribute the terms, but I have no idea what the correct forms look like because I always ended up with a slight different in the term hooked to 1/2a. Any help here?